Development of Integrated Learning Model of Soft Skills and Hard Skill in Raising the Competence of Citizens Learning Institute Courses on Beauty - Wiwin Herwina (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
This study leaves behind the problem of how the initial conditions of study at the Institute of beauty Courses, how the conceptual model of integrated learning soft skills and hard skills, how the application of integrated learning model of soft skill and hard skills, and how effectiveness. The integrated learning model of soft skill and hard skill that can improve the competence of Learning Institute courses in the field of beauty. Theories that inform the study of educational theories outside of school, learning models, integrated learning, citizens' learning competencies, and beauty courses. The approach used in this research is qualitative research approach and approach & development, research method used is description and experiment method. The results show that: (1) the initial conditions of learning in beauty institutions are still dominated by tutors, unfeeling citizens engaged in learning, (2) validation experts have produced integrated integrated learning model in improving the competence of citizens. Learning, (3) application of model can produce model of integrated learning model of soft skill and hard skill to improve citizen learning competence, (4) model of integrated learning model soft skill and hard skill developed in this research In accordance with qualitative or quantitative analysis from The results of the test results have effectively increased the competence of participants of the Institute Learning course on beauty, the conclusion of this research is that the integrated learning model of soft skill and hard skills developed has been effective in improving the competence of learning institute courses on beauty.